Tingkat Kepuasaan Siswa Terhadap Pembelajaran Pendidikan Jasmani di Masa Pandemic - Hidayat, Aldi (Jurnal Literasi Olahraga, 2022)
This study aims to determine the level of satisfaction of Class VIII students of SMP Negeri 2 Anjatan with online learning in the COVID-19 Pandemic Era 2020. This type of research is a quantitative descriptive study using a survey method. Data collection techniques in this study used a questionnaire instrument and data analysis techniques used descriptive statistics with percentages. The population in this study were 130 students of class VIII SMP Negeri 2 Anjatan using the Accidental Sampling technique with 83 students as respondents. Based on the results of research and discussion, it was concluded that the level of student satisfaction with learning PJOK online in the Covid-19 Pandemic was included in the "very satisfied" category 0 students or 0% percentage, 5 students "satisfied" category or 6.02% percentage, category "Quite satisfied" 16 students or 19.28% percentage, 36 students dissatisfied category or 43.38% percentage, 26 students "very dissatisfied" category or 31.32% percentage, so that the satisfaction of grade VIII students of SMP Negeri 2 Anjatan was classified as low.